PENINGKATAN PEMAHAMAN HASIL BELAJAR IPA MELALUI PENGGUNAAN MEDIA GAMBAR DENGAN METODE DISKUSI PADA SISWA KELAS IV DI SDN MULYAHARJA 2 - Ani Naryani; Hendro Prasetyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This classroom action research research aims to improve students' understanding of the concept of plant parts and their functions through the application of picture media with a discussion method at SDN Mulyaharja 2. Before the application of the media and method, approximately 70% of 31 students did not understand the concept. After the application of picture media with a discussion method, approximately 85% of students achieved a good understanding. The research was conducted in two cycles referring to the Kemmis and McTaggart model which includes the planning, action, observation, and reflection stages. Data were collected through pre-tests, post-tests, and student observation sheets. The results showed a significant increase in students' understanding of learning outcomes and activeness. The application of this media and method encourages collaboration, mutual teaching between students, and active involvement which are important in science learning in the Independent Curriculum. It was concluded that picture media with a discussion method improved science learning outcomes in the material of plant parts and their functions, and it is recommended to continue to be developed in science learning in elementary schools.